QARAQALPAQ LIRIKASÍNDA TUTAS KONTEKSTLI METAFORALAR (J.Izbasqanov hám B.Genjemuratov dóretiwshiligi mısalında) - Tilegenova, A.E. (SCIENCE and SOCIETY, 2025)
The article analyzes contextual metaphors in Karakalpak lyric poetry, examining examples presented in J.Izbaskanov and B.Genjemuratov’s works.